PHARMACOGENETIC TESTING OPPORTUNITIES IN CARDIOLOGY BASED ON EXOME SEQUENCING - N. V. Shcherbakova; A. I. Ershova; A. A. Suvorova; E. Y. Hlebus; A. N. Meshkov; S. A. Boytsov (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study what cardiac drugs currently have any comments on biomarkers and what information can be obtained by pharmacogenetic testing using data exome sequencing in patients with cardiac diseases. Material and methods. Exome sequencing in random participant of the ATEROGEN IVANOVO study and bioinformatics analysis of the data were performed. Point mutations were annotated using ANNOVAR program, as well as comparison with a number of specialized databases was done on the basis of user protocols. Results. 11 cardiac drugs and 7 genes which variants can influence cardiac drug metabolism were analyzed. According to exome sequencing of the participant we did not reveal allelic variants that require dose regime correction and careful efficacy control. Conclusion. The exome sequencing application is the next step to a wide range of personalized therapy. Future opportunities for improvement of the risk-benefit ratio in each patient are the main purpose of the collection and analysis of pharmacogenetic data.